2017
DOI: 10.3390/toxins9090278
|View full text |Cite
|
Sign up to set email alerts
|

Total Body Irradiation Mitigates Inflammation and Extends the Therapeutic Time Window for Anti-Ricin Antibody Treatment against Pulmonary Ricinosis in Mice

Abstract: Ricin, a highly toxic plant-derived toxin, is considered a potential weapon in biowarfare and bioterrorism due to its pronounced toxicity, high availability, and ease of preparation. Pulmonary exposure to ricin results in the generation of an acute edematous inflammation followed by respiratory insufficiency and death. Massive neutrophil recruitment to the lungs may contribute significantly to ricin-mediated morbidity. In this study, total body irradiation (TBI) served as a non-pharmacological tool to decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…Neutrophils were proposed to promote lung epithelial regeneration by enhancing type II pneumocyte proliferation (28), cells that were shown to be very sensitive to ricin at later time points, and therefore, the absence of neutrophils at that time point may undesirably exacerbate lung permeability. This may explain our finding that neutrophil depletion increased MTTD values but not the actual survival rates of anti-ricin antibody-treated mice, in a similar manner to that reported in irradiated ricin-intoxicated mice (12).…”
Section: L265supporting
confidence: 81%
See 2 more Smart Citations
“…Neutrophils were proposed to promote lung epithelial regeneration by enhancing type II pneumocyte proliferation (28), cells that were shown to be very sensitive to ricin at later time points, and therefore, the absence of neutrophils at that time point may undesirably exacerbate lung permeability. This may explain our finding that neutrophil depletion increased MTTD values but not the actual survival rates of anti-ricin antibody-treated mice, in a similar manner to that reported in irradiated ricin-intoxicated mice (12).…”
Section: L265supporting
confidence: 81%
“…Recently, we reported that sublethal total body irradiation (TBI) induced a neutropenic state, which remained stable for many days, even when the irradiated mice were subsequently exposed to ricin. The irradiated mice displayed an expanded MTTD and a mitigated inflammatory response following exposure to ricin, as compared with nonirradiated ricin-intoxicated mice (12). To further address the possible role of neutrophils in alveolar-capillary barrier impairment during pulmonary ricinosis, mice were subjected to TBI to induce neutropenia, 3 days later the irradiated mice were intranasally exposed to ricin, and 72 h later the functional integrity of the alveolar-capillary barrier was evaluated utilizing the EBD assay.…”
Section: Total Body Irradiation Mitigates Pulmonary Edema Formation Amentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of lethal ricin intoxication, rabbit-derived polyclonal anti-ricin antibody-based treatment up to three hours post exposure conferred protection to ≥90% of the mice, nonetheless following treatment at 24 hours survival rates declined dramatically, to 34% [3]. When antibody treatment was administered at 48 hours post exposure to ricin, protection was no more than marginal [5]. In sharp contrast, the administration of polyclonal anti-abrin antibodies to mice intranasally exposed to a lethal dose of abrin, led to very high survival rates (~70%-80%), even when the antibodies were applied as late as 72 hours after intoxication [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a research article from the groups of Lee and Park describes for the first time the apoptotic processes induced by Shiga toxins in human retinal pigment epithelial cells, suggesting the mechanisms leading to blindness in severe cases of hemolytic and uremic syndrome [ 8 ]. Gal et al extend their characterization of the crucial role of inflammation in ricin toxin pathogenesis by showing that total body irradiation of mice decreases inflammation markers and extends time to death [ 9 ]. Second after ricin toxin, the plant RIP abrin is considered an increasing risk of malevolent and suicidal use.…”
mentioning
confidence: 99%